ANALISIS KOMPLAIN DI UNIT CUSTOMER SERVICE OFFICER RUMAH SAKIT MUHAMMADIYAH LAMONGAN - Nanda, Diana Mei; Munaa, Nihayatul; Kusdiyana, Ari; Kusumaningrum, Candra Dewi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Introduction: The key to the success of a hospital engaged in the service sector is proven by how the company serves their customers. Every customer must have high expectations for the quality of service. Complaint handling becomes an important channel when the product produced does not match the value expected by the customer because no product, both goods and services, is without weaknesses. Purpose: This study aims to describe and analyze complaints at Hospital of Muhammadiyah Lamongan with a Lean Management approach. Methods: What the researcher uses in analyzing complaints 1) Complaint analysis, 2) Complaint identification with an element of management approach, 3) Determining problem priorities with the USG method and causes of complaint problems using the 5 Why Analysis Form, 5) Problem solving using step 7 recommendation form and action plan. Results: Recap of complaints for January-April 2023 at Hospital of Muhammadiyah Lamongan a total of 54 complaints in the green category with the priority being the problem of unfriendly officers. One of the reasons for this complaint is that the officers did not apply 5s. Conclusion: Not optimal implementation of employee ethics SOP in the hospital, socialization of employee ethics SOP was carried out. With regular dissemination of SOP so that employees understand more about the importance of SOP while working.